Flexural behavior of a UHPC slab - FRP truss hybrid beam implementing a novel FRP joint and tailored shear connector - Zhou, Jian; Feng, Yu; Huang, Xiangzhi; Wang, Jingquan; Zhong, Rui (Frontiers in Materials, 2024)
A full-scale hybrid beam consisting of a UHPC slab and FRP truss girder was fabricated. The novel side plate FRP joint characterized with improved load-carrying capacity, stiffness, and preferred failure mode along with the tailored shear connector validated in the previous studies of the authors were adopted. Its flexural performance was characterized and compared with that of hybrid beams employing NC or UHPC slab but Iprofile girder. The failure of the proposed hybrid beam subjected to bending was pseudo ductile whereas those of the other two hybrid beams were brittle. The load-carrying capacity and stiffness of the proposed hybrid beam outperformed the other two hybrid beams with comparable dimensions and material properties.